Regimekonflikt im Völkerrecht anhand des Beispiels UNHCR - IOM - Hadorn, Nina (Völkerrecht und Außenpolitik, 2023)
While many international organisations were seen as mere fora for state cooperation in their early stages, states have assigned them more and more tasks and many organisations act with increasing autonomy. Likewise, the United Nations High Commissioner for Refugees (UNHCR) and the International Organization für Migration (IOM), both dealing with migration, expanded their mandates considerably over time, which lead to duplicated efforts and competition. The book looks at conflicts from the perspective of the institutional dimension of the fragmentation of international law. Based on a case study of the UNHCR and the IOM, institutional forms of conflict are illustrated.